Determinar los requerimientos hídricos del pepino dulce (Solanum muricatum aiton) mediante el lisímetro volumétrico en la parroquia Malacatos sector El Porvenir - Paccha Silva, Melanea Andrea (2018)
The present investigation was conducted in the Rumishitana neighbourhood of the sector El Porvenir, which belongs to the Parish of Malacatos, and is located 10 km from the parish head, and 20 km from de city of Loja. The main objective of this research was to determine the water requirements of the pepino fruit (solanum muricatum aiton) for the purpose of improving the efficiency of water use. The study area comprised 48 m2, in which two lysimeters of 1 m2 were installed. The crop that was sown was the pepino fruit with a planting density of 1 m between rows and 0.50 m between plants. The phenological phases for the 199-day period were: vegetative growth 56 days, flowering 21 days, fruit development 87 days and harvest 35 days. For the evapotranspiration of the reference crop (Eto) an average value of 3.93 mm/day was obtained and the crop evapotranspiration (Etc) was estimated to be 3.23 mm/day. The Kc values obtained for the cultivation of the pepino fruit were: 56 days kc=0.72 vegetative growth phase; 21 days kc= 0.83 flowering phase; 87 days kc=0.88 fruit development phase; and 35 days kc=0.85 in the harvest phase. The total water requirement was 645.72 mm which is equivalent to 6457.2 m3/ha ha with a yield of 71.161 ton/ha, the water consumption/ yield ratio leads to the conclusion that, to obtain 1 kg of the pepino fruit, 90.7 litres of water are required. Keywords: Lysimeter, Evapotranspiration, Water requirements, Coefficient of cultivation